Lukácsian aesthetics in a post-modern world: understanding Thomas Pynchon’s Mason & Dixon through the lens of Georg Lukács’ the historical novel - Dvorak, John N. (Kansas State University, 2010)
This thesis project seeks to reconcile the literary criticism of Marxist critic and advocate of literary realism Georg Lukács with the writing of postmodern author Thomas Pynchon in order to validate the continued relevance of Lukácsian aesthetics. Chapter 1 argues that Lukács’ The Historical Novel is not only a valid lens with which to analyze Pynchon’s own historical novel, Mason & Dixon, but that such analysis will yield valuable insight. Chapter 2 illustrates the aesthetic transition from the historical drama to the historical novel by using Lukács’ ideas to explicate The Courier’s Tragedy, a historical drama found within the pages of Pynchon’s The Crying of Lot 49. Chapter 3 applies Lukács’ ideas on the “world-historical” figure and the “mediocre” hero of the classic historical novel to Mason & Dixon. Chapter 4 asserts that Mason & Dixon enables contemporary readers to experience the novel as what Lukács calls a “prehistory” to the present. This chapter also illustrates how the prehistory of Mason & Dixon anticipates Pynchon’s nonfiction essay “A Journey into the Mind of Watts.” Finally, this chapter demonstrates how Pynchon avoids the pitfall of modernization in Mason & Dixon, which Lukács defines as the dressing up of contemporary crises and psychology in a historical setting. Chapter 5 ties together the work of the previous four chapters and offers conclusions on both what Pynchon teaches us about Lukács, as well as what Lukács helps us to learn about Pynchon.
Keywords: Thomas Pynchon; Georg Lukacs; The Historical Novel; Postmodernism; Mason & Dixon; Marxist Literary Criticism; Literature, English (0593)